Smart Mirror for Home Automation - Ab Latif, Muhammad Syazwan; Ismail, Ammar Asyraf; Zariman, Asnazulfadhli (International Journal of Recent Technology and Applied Science (IJORTAS), 2019)
Smart Mirror for Home Automation This research describes the design, construction and working of the smart mirror. Every morning our day begins by watching ourselves at least once in mirror before leaving our homes. We interact with it psychologically to find out how we look and how our attire is. Smart Mirror or Magic Mirror is one of the applications of Raspberry Pi. A computer screen embedded in mirror looks very futuristic. The Raspberry Pi stays at back scenes and controls the data displayed on mirror. While looking at mirror, the user can look at various notifications from social sites as well news, weather forecast and more things. Such mirrors can be programmed to work as control home appliances by voice input. The Raspberry Pi is connected to monitor via HDMI as well as it also has built-in Wi-Fi and Bluetooth interfaces so we can just swipe music and videos to mirror.